2014
DOI: 10.1007/s10661-014-3910-7
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of universal Bacteroidales genetic marker for microbial monitoring of drinking water sources in comparison to conventional indicators

Abstract: Water quality monitoring is essential for the provision of safe drinking water. In this study, we compared a selection of fecal indicators with universal Bacteroidales genetic marker to identify fecal pollution of a variety of drinking water sources. A total of 60 samples were collected from water sources. The microbiological parameters included total coliforms, fecal coliforms, Escherichia coli and fecal streptococci as the fecal indicator bacteria (FIB), Clostridium perfringens and H2S bacteria as alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Moreover, it was observed that a signi cant difference existed between clostridium perfringens and fecal coliform and fungi. A similar result was seen between total coliform and clostridium perfringens and fungal species (Mhlongo et al, 2019;Mirshekar et al, 2019;Shahryari, Nikaeen, Khiadani, et al, 2014). Of course, it is important to note that false-positive and false-negative results were seen between measured microorganisms.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Moreover, it was observed that a signi cant difference existed between clostridium perfringens and fecal coliform and fungi. A similar result was seen between total coliform and clostridium perfringens and fungal species (Mhlongo et al, 2019;Mirshekar et al, 2019;Shahryari, Nikaeen, Khiadani, et al, 2014). Of course, it is important to note that false-positive and false-negative results were seen between measured microorganisms.…”
Section: Resultssupporting
confidence: 68%
“…The positive sample was subcultured anaerobically on Tryptose Sulphite Cycloserine (TSC) agar and formation of colonies of yellow-brown, grey or black on TSC was reported as positive. The con rmed test was then performed using gram staining, motility and nitrate reduction (Shahryari, Nikaeen, Khiadani, et al, 2014). The numbers of total and fecal coliforms, fecal streptococci and Clostridium perfringens were counted using a 10.0-tube table as the Most Probable Number (MPN) per 100.0 ml (APHA, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HC-71 and JR-18 with a high adhesion ability were close, located between the positive axis of PC1 and the negative axis of PC2; HR-15 was located between the positive axis of PC1 and PC2; while the similarity of con0 and con6 in the control group were close, indicating that the addition of S. putrefaciens significantly affected the flora composition and had a certain relationship with the adhesion ability of the strains. Bacteroidales, a common pathogen of fish [21]. On day 6 of storage, the differential bacteria in the control group changed into Lactococcus and Acidisphaera.…”
Section: S Putrefaciensmentioning
confidence: 99%
“…Cetobacterium is a common bacterium in fish. Barnesiellaceae mostly comes from water pollution including Bacteroidales, a common pathogen of fish [21]. On day 6 of storage, the differential bacteria in the control group changed into Lactococcus and Acidisphaera.…”
Section: S Putrefaciensmentioning
confidence: 99%